Review on Information Retrieval for Desktop Search Engine - Akshay, Akshat Divya; Nikhil, Jammula; Chowdhury, Arindam; Karthik, S. A. (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Search is an important aspect of information management often taken for granted. Domain specific repositories are growing in both size and numbers calling for efficient search and retrieval of documents. This paper explores the possible techniques and necessary system components for a search engine charting several iterative optimizations over the last few years. This paper focuses on NLP models while retaining basic principles from other methods that assist in information search.